Respuesta :

Answer:

[tex]D. (3,-1)[/tex]

Step-by-step explanation:

[tex]x + y = 2 \: \: \: \: \: \: ..(1) \\

2x - y = 7 \: \: \: \: ..(2)[/tex]

from equation 1 we get,

[tex]x = 2 - y[/tex]

now,

[tex]put \: \: \: \: x = 2 - y \: \: \: in \: (2)[/tex]

we get,

[tex]2(2 - y) - y = 7 \\ 4 - 2y - y = 7 \\ 4 - 3y = 7 \\ - 3y = 7 - 4 \\ - 3y = 3 \\ \\ y = \frac{3}{( - 3)} \\ \\ y = - 1[/tex]

now,

[tex]put \: \: \: \: y = - 1 \: \: \: \: in \: (1)[/tex]

we get,

[tex]x + ( - 1) = 2 \\ x - 1 = 2 \\ x = 2 + 1 \\ x = 3[/tex]

hence, the value of x = 3 and y = (-1)

ACCESS MORE